Preparation and application of collagen keratoprosthesis with heterogeneous fiber microstructure

By controlling humidity and electrical signals to regulate collagen assembly, and combining photocrosslinking technology, collagen artificial cornea with heterogeneous fiber microstructure was prepared, which solved the difficulty of taking into account the high transparency and suture resistance of synthetic materials when imitating natural corneas. Problem, efficient preparation of materials with excellent optical and mechanical properties is achieved.

CN119139549APending Publication Date: 2024-12-17EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411128740.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing synthetic collagen materials face the problem of high transparency and suture resistance when imitating natural corneal structures, and the self-assembly process of collagen molecules in vitro is difficult to control, resulting in the visual opaque and poor mechanical properties of the formed materials.

Method used

By controlling humidity and electrical signals, the kinetic assembly of collagen is controlled to form a high-density collagen network with crystalline crude fiber structure. Combined with photocrosslinking technology, collagen artificial cornea with heterogeneous fiber microstructure is prepared to achieve fiber diameter control and mechanical properties improvement.

Benefits of technology

It has achieved efficient preparation of collagen-based artificial corneals with high transparency and good suture properties in vitro, simulated the structural and functional characteristics of the natural corneal and sclera, and significantly improved the optical and mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119139549A_ABST
    Figure CN119139549A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of tissue repair in biomedical materials, and relates to an artificial cornea with a heterogeneous fiber microstructure and a preparation method and application thereof. The preparation method of the collagen artificial cornea with the heterogeneous fiber microstructure comprises the following steps: dissolving type I collagen, and forming a collagen membrane assembled by electric field triggering dynamics through an electro-deposition reaction; covering a preset template on the collagen membrane assembled by the electric field triggering dynamics, and exposing the collagen membrane under an ultraviolet light source for crosslinking; placing the collagen membrane assembled by the electric field triggering dynamics in a constant temperature and humidity chamber, and inducing continuous thermodynamic assembly of the collagen; the temperature in the constant-temperature and constant-humidity box is 4-45 DEG C, the time is 3-30 hours, water or a water-containing solution is placed in the constant-temperature and constant-humidity box, and the relative humidity is controlled to be 40%-100%. According to the artificial cornea, the fiber diameter and the compact stacking state of the collagen assembly are considered, and the suture performance requirement is met while the good transparency is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of tissue repair in biomedical materials, and relates to an artificial cornea with a heterogeneous fiber microstructure, a preparation method and application thereof. The present invention also relates to a high-stacking-density collagen material as a raw material for preparing the artificial cornea with a heterogeneous fiber microstructure, and a preparation method and application thereof. Background Art

[0002] Corneal transplantation is the main treatment option for corneal blindness rehabilitation in clinical practice. Due to the severe shortage of donor corneal tissue, my country completes about 5,000 transplant operations each year, accounting for only 1 / 40 of the total number of patients. Clinically, artificial corneal transplants (ACS) are urgently needed to replace human donations. As early as the 1990s, the US patent application with publication number US5067961A designed a non-biodegradable corneal implant, which includes: (1) a central transparent area with acylated amine or esterified carboxyl groups, and (2) a fibrous, opaque peripheral area surrounding the core. In theory, the cornea can be implanted and have properties similar to those of a natural cornea.

[0003] Existing ACS can be roughly divided into two categories based on material composition, namely, animal-derived decellularized matrix ACS and synthetic polymer ACS. The two animal-derived decellularized ACS on the Chinese market, such as Shenzhen Aixintong and Guangzhou Youdeqing, face many challenges, such as complex decellularization process, antigenicity, immune rejection and lack of transparency, and there is also the risk of spreading animal diseases. On the other hand, common problems of ACS based on synthetic polymers include poor compatibility with ocular tissues and inability to integrate with host tissues. These problems may lead to severe inflammation and angiogenesis, affecting the normal function of the cornea. Therefore, ACS materials with excellent ocular tissue compatibility are an important research topic in this field.

[0004] Natural corneal tissue is composed of numerous collagen fibers that are closely arranged and crisscrossed into a network. Collagen is undoubtedly the most ideal raw material for ACS. Collagen is assembled in order from triple helical molecules in the body, forming mature fibers with different orderly arrangements from nanometers to micrometers to perform different physiological functions. Taking the cornea and sclera tissue of the eyeball as an example, the unique microstructure of collagen not only gives the cornea a high degree of transparency, but also provides the necessary mechanical support for the sclera. The microstructure of collagen fibers in the cornea in the middle area of ​​the eyeball wall and the sclera at the edge show significant differences. Among them, the cornea is composed of uniform small-diameter collagen microfibrils arranged in layers, showing high transparency to allow light to enter, thereby meeting the visual function; while the sclera is composed of widely distributed large-diameter collagen fibers, showing optimized mechanical properties to provide structural support and protection for the eyeball. Generally, collagen molecules can be guided by endogenous signals in the body to assemble hierarchically and orderly in a confined space to form a specific internal microstructure, thereby achieving high light transmittance and strong mechanical properties. By mimicking the internal microstructural features of the cornea and sclera, the optical and mechanical properties of synthetic collagen materials can be effectively improved, providing a feasible solution for manufacturing collagen-based ACS materials with excellent optical properties (i.e., high transparency and low haze) and capable of surgical suture.

[0005] The invention of US Patent No. 5067961 designs a non-biodegradable corneal implant comprising (1) a central transparent region having acylated amine or esterified carboxyl groups and (2) a fibrous, opaque peripheral region surrounding the core. A method for preparing the implant is also provided and validated in penetrating keratoplasty to study the results of transparency, inflammation, and re-epithelialization of the implant.

[0006] However, current synthetic collagen materials face many challenges in mimicking these natural structures, including: In vitro, the self-assembly of collagen molecules is a typical thermodynamic endothermic process in an unconfined space, which tends to aggregate fibrils to form larger fiber structures with highly loose and irregular arrangement, resulting in a strong scattering effect on the incident light. The resulting collagen materials are visually opaque or translucent, and have poor mechanical properties, which cannot meet the requirements for suturing. How to control the hierarchical assembly process of collagen in vitro at the molecular level, thereby controlling its internal microstructure, is the entry point for biomimetic manufacturing of highly transparent and sutureable collagen-based artificial corneas. Summary of the invention

[0007] The technical problem to be solved by the present invention is to enable the artificial cornea to maintain high transparency and good suture resistance at the same time.

[0008] In view of the above problems, on the one hand, the present invention provides a collagen artificial cornea with a spatially heterogeneous collagen fiber network, which controls the diameter of the assembled fibers while maintaining the dense stacking state of the fibers. The diameter of the collagen fibers can reach 500nm, and the stacking density of the collagen network is about 230mg / cm 3 .

[0009] The present invention controls the humidity, i.e. limits the participation of water molecules, and regulates the microstructure of the collagen assembly, thereby mimicking the hierarchical assembly process of collagen in a confined space environment in vivo. In a crowded environment, water molecules are limitedly retained between collagen molecules, which helps to form hydrogen bonds, triggering intermolecular aggregation and nucleation to trigger fiber formation, while the partial dehydration effect can promote a tighter combination between collagen molecules / fibers and promote the growth of its fibers. At the same time, the collagen microfibers obtained by kinetic assembly are used as the starting point for thermodynamic assembly, so that the fiber size can be controllably transformed from the nanoscale (about 10nm) to the mesoscale, and the final fiber diameter can reach 400-500nm, thereby constructing a mechanically reinforced collagen network with a crystalline coarse fiber structure. By using electrical signals to initiate the kinetic assembly of collagen molecules, a high-density collagen gel network can be prepared in a time-saving and efficient manner, with a density of up to 450mg / cm 3 Compared with traditional methods of increasing collagen density, the preparation time is greatly shortened and the tissue density is greatly improved.

[0010] On the other hand, the present invention provides a method for preparing the above-mentioned heterogeneous fiber microstructure collagen artificial cornea (which may be referred to as artificial cornea in the present invention). The dynamic-thermodynamic relay collagen and high stacking density collagen material can be obtained by controlling the photocrosslinking conditions. Specifically, the mask is covered on the kinetically assembled collagen (also referred to as AMF-Col), and then exposed to an ultraviolet light source for crosslinking to fix the customized area. The customized area that is photocrosslinked maintains the original fiber microstructure unchanged during the subsequent thermodynamic assembly process, and the area that is not photocrosslinked forms large-scale fibrils during the assembly process.

[0011] Preferably, the method for preparing the heterogeneous fiber microstructure collagen artificial cornea comprises:

[0012] (1) dissolving type I collagen and forming an electric field-triggered kinetically assembled collagen film through electrodeposition reaction;

[0013] (2) Covering the collagen film with electric field-triggered dynamic assembly with a preset photomask and then exposing it to a UV light source for local photocrosslinking;

[0014] (3) Placing the collagen film that has undergone local photocrosslinking under constant temperature and humidity conditions to induce the continuous assembly of uncrosslinked collagen: placing it under constant temperature and humidity conditions for 3-30 hours at a temperature of 4-45° C. and a relative humidity of 40%-100% in the constant temperature and humidity space.

[0015] Preferably, inducing the continuous assembly of the collagen film comprises: placing the collagen film in a constant temperature and humidity environment (e.g., a constant temperature and humidity chamber) to induce the continuous assembly of the collagen film; the temperature in the constant temperature and humidity chamber is 25-40°C, more preferably, the temperature is 30-37°C, for example, the temperature is 32, 33, 34, 35, 36°C. The time is 12-36 hours, more preferably, the time is 12-30 hours, for example, the time is 18-24 hours.

[0016] Preferably, the relative humidity is controlled to be 40%-100%, more preferably 40%-60% or 60%-80%. Water or a water-containing solution is placed in the constant temperature and humidity chamber, preferably an ammonium salt solution is placed. For example, the ammonium salt solution placed in the constant temperature and humidity chamber is NH4HCO3 solution, and the concentration is 50mM-200mM. More preferably, the concentration is 100mM-150mM, such as 80mM, 120mM, 130mM, 140mM, 160mM, etc.

[0017] As shown in the experimental results of the present invention, the suture strength of the collagen assembly obtained after assembling for 24 hours at a temperature of 37°C and a humidity of 60% is 4.69N / mm, and the tensile strength is 5.97MPa. The suture strength of the assembly assembled for 24 hours at a temperature of 4°C and a humidity of 60% is 1.83N / mm, and the tensile strength is 3.59MPa; the suture strength of the assembly at a temperature of 25°C, constant humidity and time is 2.58N / mm, and the tensile strength is 4.42MPa; the suture strength of the collagen assembly assembled for 24 hours at a temperature of 37°C and a humidity of 40% is 3.23N / mm, and the tensile strength is 5.34MPa; the suture strength of the assembly at a temperature of 80% and constant humidity is 2.69N / mm, and the tensile strength is 4.23MPa.

[0018] Preferably, the kinetic-thermodynamic relay collagen assembly, or collagen membrane, comprises at least two steps in its preparation method: first, kinetic assembly of collagen, and then thermodynamic assembly. After the kinetic assembly of collagen, thermodynamic assembly is performed, i.e., the continued assembly process under the preferred conditions in the constant temperature and humidity chamber described above is called "relay thermodynamic assembly of collagen". The two steps are collectively referred to as "kinetic-thermodynamic relay assembly" to obtain the final collagen assembly.

[0019] The following preparation process is called "kinetic assembly of collagen":

[0020] Dissolve type I collagen, add glacial acetic acid to make its pH acidic; add hydrogen peroxide to obtain collagen electrolyte;

[0021] The three-electrode system of electrodeposition is used to establish a pH gradient by utilizing electrode reaction, so that the collagen undergoes a phase transition, from a collagen solution to a collagen gel membrane AMF-Col.

[0022] The reaction equations at the anode and cathode are as follows:

[0023] Anode: 2H2O–4e - →4H + +O2;

[0024] Cathode: 2H2O+4e - →4OH-+2H2.

[0025] The obtained collagen membrane is a collagen gel membrane with a very uniform appearance, which is highly transparent in both dry and wet states, and is composed of short-range oriented collagen microfibrils connected by non-covalent bonds; the collagen is densely arranged; the material has a transparent appearance and a uniform structure.

[0026] The collagen gel film can be directly obtained on the electrode and can be peeled off from the electrode after preparation. For details, please refer to the Chinese invention patent with application number 202210102037.X. The preparation process can be carried out according to the following steps:

[0027] S1. Preparation of collagen solution: Add acetic acid to the collagen solution to completely dissolve the collagen, adjust the pH value of the final solution to 1.5-4, and obtain a collagen solution with a concentration in the range of 1-20 mg / ml after concentration.

[0028] S2, adding hydrogen peroxide to the collagen solution obtained in step S1 to make the final concentration in the solution be 5-200 μl / ml, stirring, removing bubbles, and placing at 0-10° C. for standby use; optionally, the amount of hydrogen peroxide added is 5-17%.

[0029] S3, using a titanium sheet as a working electrode and platinum as a counter electrode, the two electrodes are placed in parallel in an electrolytic cell with the distance between the electrodes controlled at 0.5-3.0 cm, and the collagen solution prepared in step S2 is slowly added to the electrolytic cell.

[0030] S4, using constant voltage or constant current deposition to carry out electrochemical reaction, the deposition time is 10-120 minutes, and a collagen gel film deposited on the cathode is obtained.

[0031] In the present invention, cross-linking can be performed by photo-crosslinking or glutaraldehyde cross-linking. The photo-cross-linking refers to immersing the collagen membrane in a 0.2-3.0 mg / ml riboflavin solution and cross-linking for 1-3 days under ultraviolet light. The riboflavin solution uses 90% v / v ethanol-water as a solvent, has a concentration of 0.5-2.0 mg / ml, and a cross-linking time of 20-40 hours.

[0032] The glutaraldehyde cross-linking means that the collagen membrane is immersed in a 0.1%-1% (volume percentage) glutaraldehyde solution, cross-linked for 10 minutes to 2 hours, and then the residual glutaraldehyde component in the collagen membrane is removed. The glutaraldehyde solution uses 0.5% w / v, 90% v / v ethanol-water as solvent, and the cross-linking time is 30-50 minutes.

[0033] Optionally, to remove the cross-linking agent components, such as glutaraldehyde, etc., remaining in the collagen membrane, ultrapure water may be used for repeated rinsing, for example, 3-5 times.

[0034] In the present invention, ultrapure water is also called UP water, which is water with a resistivity of 18MΩ*cm (25°C). In addition to water molecules, this water has almost no impurities, no mineral trace elements, and no bacteria, viruses, chlorinated dioxins and other organic substances. When ultrapure water is treated, the conductive medium in the water is almost completely removed, and the undissociated colloid substances, gases and organic substances in the water are removed to a very low level. It usually requires four steps: pretreatment, reverse osmosis technology, ultrapurification treatment and post-treatment.

[0035] In the preparation method of the heterogeneous fiber microstructure collagen artificial cornea of ​​the present invention, the dynamic-thermodynamic relay collagen assembly method is combined with the photomask technology to achieve the spatial heterogeneity control of the collagen fiber network. This will allow the integration of different microstructures in the same material, thereby simulating the structural and functional characteristics of the natural cornea and sclera.

[0036] The kinetic-thermodynamic relay collagen assembly of the present invention can be used in the repair of corneal lamellar defects in vivo. The heterogeneous fiber microstructure collagen artificial cornea is directly used as an implant material for corneal defect repair, which can promote the migration of corneal epithelial cells to the defect site, thereby achieving epithelialization of the corneal defect site. At the same time, it helps the regeneration of the corneal stroma layer, so that the cornea can be restored to a healthy level.

[0037] In the present invention, RH stands for relative humidity.

[0038] In the present invention, AMF-Col is the abbreviation of the collagen assembly obtained by the dynamic assembly method under electric field regulation, and its interior is composed of tightly packed nano-microfibers (about 10 nm), which makes it have excellent optical transparency and highly transparent appearance.

[0039] Since the collagen microfibrils obtained by dynamic assembly have the potential to continue to assemble, AMF-Col can continue to assemble by thermodynamic means. CF-Col is the abbreviation of the collagen assembly obtained by relay thermodynamic assembly of AMF-Col under constant temperature and humidity conditions. Its interior is composed of widely distributed collagen fibers with a large diameter of 400-500nm. The appearance is milky white, with poor optical transparency and visually opaque.

[0040] In the present invention, ACS is the abbreviation of Artificial Cornea Implant.

[0041] In the present invention, HFs-ACSs is the abbreviation of heterogeneous fiber microstructure collagen artificial cornea (prepared under RH of 60%). The artificial cornea imitates the internal microstructure characteristics of the natural cornea and sclera, that is, the middle core area is composed of nano-microfibers with smaller diameters, providing excellent optical properties, and the outer ring area is composed of widely distributed large-diameter collagen fibers, providing mechanical properties that are resistant to surgical suturing. The artificial cornea achieves a highly transparent, sutureable, integrated and controllable construction.

[0042] The beneficial effects of the present invention include:

[0043] First, spatial regional microstructure regulation: Existing collagen assembly technologies are usually homogeneous, and it is not possible to spatially control the collagen assembly microstructure to customize local characteristics like biology, and ultimately achieve integrated diverse biological functions. The present invention realizes the integration of the integrated functions of different fiber microstructures in the whole collagen material through the dynamic-thermodynamic relay assembly technology and the photomask technology in series. The present invention realizes the spatial heterogeneity control of the collagen fiber network through the dynamic-thermodynamic relay assembly technology combined with the photomask technology, and integrates: i) uniform small-diameter collagen microfibers with dense layer arrangement, and ii) widely distributed large-diameter collagen fiber structure, while achieving local high transparency and showing optimized mechanical properties.

[0044] Second, it can save time and efficiently reproduce collagen hierarchical assembly structures with high packing density in vitro: Compared with the previously reported methods for increasing the concentration of collagen assembly in vitro, the method of initiating the kinetic assembly of collagen by electrical signals proposed in the present invention can save time and effectively prepare collagen assemblies with high packing density. The fiber structure in the collagen network of the present invention ranges from the nanoscale (~1-100nm) to the mesoscale (~100-1μm), constructing a mechanically reinforced collagen network with a crystalline coarse fiber structure. In this way, the dense stacking state of the fiber network is maintained while controlling the diameter of the assembled fibers, thereby maximizing the mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, each drawing in the following description is for some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0046] Figure 1 Kinetic assembly and characterization of type I collagen initiated by electrical signals.

[0047] (ab) Macroscopic images of type I collagen solution and schematic diagram of kinetic assembly initiated by electrical signals. The electrical signal drives the positively charged triple-helical collagen molecules to move toward the cathode and assemble into an AMF-Col hydrogel network composed of amorphous fibrils. (c) Optical microscopic image of the kinetic assembly process of Col in real time in the microchannel. (de) Two-dimensional SAXS images of Col solution and AMF-Col and (f) one-dimensional SAXS curves. The peak width of AMF-Col in the curve becomes narrower, indicating the concentration of its Col molecules in the gel phase. (g) Macroscopic image of kinetically assembled AMF-Col. (h) Low-magnification and high-magnification transmission electron microscopy images of AMF-Col. The low-magnification TEM shows the dense organization of the amorphous microfibrils inside, and the high-magnification TEM shows the thin diameter of the microfibrils. (i) Macroscopic image of the highly transparent AMF-Col and its high transmittance and low haze, which remain unchanged after UV / riboflavin cross-linking. (j) Schematic diagram of the dynamic interactions inside the collagen network. (k) Dynamics of AMF-Col, which rapidly dissolved in 0.1M HAc or 0.1M urea, indicating the existence of reversible interactions within AMF-Col. (l) Self-healing of AMF-Col, AMF-Col exhibited self-healing properties due to the reversible internal interactions.

[0048] Figure 2 Relay thermodynamic assembly of AMF-Col under humidity regulation in vitro.

[0049] (a) Schematic diagram of AMF-Col incubated at 37°C for 24 h under different humidity conditions. (b) Water content and (c) collagen density changes of AMF-Col after incubation at 37°C for 24 h under different humidity conditions. (d) Macroscopic and microscopic images of AMF-Col and CF-Col prepared under different humidity conditions. (e) Quantification of collagen tissue density, (f) average fiber diameter, and (g) fiber distribution in CF-Cols. (h) One-dimensional SAXS curves of CF-Cols further indicate their different degrees of crystallinity. (i) Suture-pullout curves and (j) tensile stress-strain curves of AMF-Col and CF-Cols, and (k) comparison of their tensile strength, modulus, toughness, suture resistance, and fracture capacity.

[0050] Figure 3 Relay thermodynamic assembly of AMF-Col under in vitro temperature regulation

[0051] (a) Optical density values ​​of CF-Col during incubation at 60% RH and different temperatures monitored by UV-visible spectrophotometer. (b) Representative SEM images and (c) one-dimensional SAXS curves of CF-Col obtained after AMF-Col was incubated at 60% RH and different temperatures for 24 h. (d) Quantification of the average diameter of collagen fibers and (e) fiber diameter distribution. (f) Representative suture pull-out curves and (g) tensile stress-strain curves of CF-Col incubated at different temperatures, and (h) comparison of their tensile strength, modulus, toughness, suture resistance, and fracture capacity.

[0052] Figure 4 Relay thermodynamic assembly of AMF-Col under time regulation in vitro

[0053] (a) Representative SEM images and (b) one-dimensional SAXS curves of CF-Col obtained after AMF-Col was incubated at 60% RH and 37°C for different time periods, (c) average diameter of collagen fibers, and (d) quantification of fiber diameter distribution. (e) Representative suture pull-out curves and (f) tensile stress-strain curves of CF-Col incubated for different time periods, and (g) comparison of tensile strength, modulus, toughness, suture resistance, and fracture capacity between them.

[0054] Figure 5 Customizable heterogeneous fibrous microstructured collagen materials (HFs-Col) with programmable optical windows and integration of mechanics.

[0055] (a) Schematic diagram of the preparation of collagen heterogeneous fiber microstructures. (b) Multiscale structural characterization of HFs-Col. (bi) Optical photograph of HFs-Col prepared using the "ECUST" mask; (b-ii) Magnified optical microscope image of the word "U" area; (b-iii) 2D confocal image of the "U" boundary; (b-iv) 3D confocal, SEM, AFM and 2D SAXS images of the inside of the "U"; (b-v) Image of the outer area of ​​the "U"; (b-vi) Roughness of the left and right parts of the "U" boundary. The inside of the "U" presents a smooth amorphous surface, while the outside presents a rougher fiber surface with crystalline features. (c) Macroscopic photograph of the mask with customizable optical windows and the corresponding collagen heterogeneous material. (d) Mechanical property evaluation of the collagen heterogeneous material with customizable optical windows. (di) Stress-strain curves of AMF-Col, CF-Col and patterned HF-Col in two perpendicular directions and the corresponding tensile strength and Young's modulus; (d-ii) Suture-pullout curve of HF-Col, showing mechanical changes when passing through different regions.

[0056] Figure 6 Cytocompatibility and cell migration of AMF-Col and CF-Col.

[0057] (a) Adhesion of corneal epithelial cells (HCECs) on AMF-Col and CF-Col surfaces after 24 hours of inoculation. (b) Quantitative analysis of the cell aspect ratio, indicating that the fiber structure may affect the morphology of the cells. (c) Live / dead staining fluorescence images of HCECs after 1, 3, and 5 days of culture and (d) CCK-8 assay quantitative data, indicating that the material group did not show obvious cytotoxicity. (e) Migration photos of HCECs on AMF-Col, CF-Col, and the scratch area of ​​the well plate on days 0, 1, 2, and 3, and (f) quantification of the migration area ratio, showing that both AMF-Col and CF-Col promoted faster cell migration compared with the well plate, indicating that this collagen material is beneficial for the repair of the corneal epithelium in vivo.

[0058] Figure 7 In vivo implantation and postoperative observation of bionic HF-ACSs in rabbit corneal defects.

[0059] (ab) Preparation of corneal defect model (7 mm in diameter, 200 μm in depth) and HF-ACSs implantation repair and re-epithelialization scheme. (c) Representative slit lamp photos and sodium fluorescein staining images of corneas after implantation of HF-ACSs or commercial decellularized porcine corneas (CM) at different time points. The gradual reduction of the stained area indicates that epithelial cells migrate to the defect area for repair. (de) The vascular area ratio and corneal epithelialization rate after implantation of HF-ACSs and CM indicate that HF-ACSs have better ocular tissue compatibility and epithelialization-promoting effects. (f) Representative corneal anterior segment optical coherence tomography (AS-OCT) images at different times after surgery. The boundary between HF-ACSs and CM and natural tissue was indistinguishable 4 weeks after surgery, and the cornea was completely epithelialized after 8 weeks. The dotted box indicates the transparent corneal epithelial tissue filling the stromal defect area observed in the control group after surgery. (g) Corneal topography of healthy rabbit eyes (i) and (ii) after surgery, (iii) representative corneal topography of rabbit eyes without implantation and implanted with (iv) HF-ACSs and (v) CM 8 weeks after surgery. (h) Quantitative data of corneal thickness in different experimental groups. The results showed that ACSs transplantation helped to restore corneal thickness to normal levels.

[0060] Figure 8 Histological analysis and visual recovery evaluation of ACSs implanted in rabbit corneal defect model 8 weeks later.

[0061] (a) H&E staining images of healthy corneas, corneas without implanted materials, and corneas implanted with HF-ACSs or CM. (bc) Fluorescence staining images of healthy corneas, corneas without implanted materials, and corneas implanted with HF-ACSs or CM. The results show that both ACSs can effectively support complete epithelial regeneration after implantation, but CM significantly induces α-SMA expression, which may cause corneal scarring. (d) Quantification of corneal epithelial thickness and (e) stromal thickness. (fg) Quantification of fluorescent staining areas of α-SMA and ZO-1 in fluorescent images. (h) Schematic diagram of foraging behavior of New Zealand white rabbits 28 days after surgery. (i) Representative foraging images in the foraging behavior experiment, (j) average foraging time, and (k) average foraging path. The results show that the HF-ACSs implanted group reached the target position in a shorter time and path, similar to the healthy group, indicating that vision was effectively restored after implantation.

[0062] Fig. 9 Bionic collagen substitute with heterogeneous fiber microstructure. The upper left corner is a schematic diagram of the appearance of the implanted artificial cornea. The upper right corner is a schematic diagram of the cornea-sclera area of ​​the eyeball. The circled part is the cornea area that provides visual function, and the rest is the sclera area that provides mechanical support. The lower left corner is a microstructure image of the optical area in the heterogeneous fiber microstructure artificial cornea. The lower right corner is a microstructure image of the mechanical area in the heterogeneous fiber microstructure artificial cornea. DETAILED DESCRIPTION

[0063] The existing collagen membrane has collagen microfibers with smaller diameters inside, which shows the problem of poor suturing performance. In order to improve the mechanical properties of the collagen membrane, the present invention further assembles the collagen microfibers into collagen fibers with larger diameters and wider distribution, so that they can withstand surgical suturing. Due to the large fiber diameter, the probability of light scattering will increase during the light transmission process, and some transparency will be lost, and its excellent optical properties cannot be maintained. An artificial cornea with a core skirt structure is constructed by biomimetic natural cornea-sclera microstructure. The artificial cornea has high light transmittance, provides visual function, and can provide mechanical properties that can be sutured.

[0064] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0065] Example 1: Configuration of electrolyte

[0066] 100 mg of type I collagen extracted from pig skin was weighed and dissolved in 10 mL of ultrapure water. Glacial acetic acid was added to fully dissolve it. The final pH of the solution was adjusted to 3.5 to obtain a collagen solution with a concentration of 10 mg / mL ( Figure 1 a). Add hydrogen peroxide to the solution at a volume ratio of 10:1 between collagen solution and hydrogen peroxide, stir for 5 minutes to mix evenly, centrifuge to remove bubbles in the solution, and then store the electrolyte in an ice-water mixed bath to prevent the decomposition of hydrogen peroxide in the solution due to high temperature while waiting for use.

[0067] Example 2: Preparation of collagen membrane AMF-Col by electrochemical deposition method

[0068] A three-electrode system (CHI660E) was used for electrodeposition, with a titanium sheet (size 2 cm × 3 cm) as the working electrode, a platinum wire as the counter electrode, and Ag / AgCl as the reference electrode. The three-electrode system was inserted into a pre-configured electrolyte and connected to an electrochemical workstation. The experiment was conducted in constant current mode, with a current of 40 mA (current density of 6.67 mA / cm 2 ,), deposition 500s. The corresponding electrode reaction is as follows:

[0069] Anode: 2H2O-4e - →4H + +O2;

[0070] Cathode: 2H2O+4e - →4OH- +2H2

[0071] The pH gradient was established using the electrode reaction described above ( Figure 1 b). After the reaction is completed, the titanium sheet is removed from the electrolyte, and the gel film attached to the titanium sheet is rinsed with ultrapure water to remove excess electrolyte on the surface, and then the gel film is peeled off from the electrode for subsequent testing ( Figure 1 g).

[0072] Example 3: Characterization of microscopic morphology

[0073] The internal structure of AMF-Col prepared in Example 2 was observed using a transmission electron microscope. The collagen membrane was initially dehydrated using a graded series of ethanol and embedded in Eponate 12 resin. A 60-90 nm slice was placed on a bare copper grid and then stained with uranyl acetate and lead. The image was taken at an accelerating voltage of 80 kV. Low-power and high-power transmission electron micrographs intuitively show the dense organization of microfibrils with a diameter of approximately 10 nm in AMF-Col, and no obvious D band formation was observed on the collagen microfibrils ( Figure 1 h).

[0074] Example 4: Optical Performance Characterization

[0075] The AMF-Col prepared in Example 2 was immersed in ultrapure water for 1 hour to saturate its water content, and its transmittance in the wavelength range of 400-800nm ​​was measured. The results showed that it showed high transmittance (nearly 90%) and low haze (less than 20%) in the visible light region, and the optical properties of high transmittance and low haze were still maintained after UV / riboflavin covalent cross-linking.

[0076] Example 5-7: Dynamic Characterization of AMF-Col

[0077] Example 5: The AMF-Col prepared in Example 2 was dyed with Alizarin Red and placed in a 0.1M acetic acid aqueous solution or a 0.1M urea solution at pH 3.5. After a period of time, it was observed that the AMF-Col rapidly dissolved ( Figure 1 k).

[0078] Example 6: The AMF-Col prepared in Example 2 was cut vertically and re-bonded after being exposed to the air at 37°C for 48 hours, which proved that there was a reversible interaction inside the AMF-Col. Figure 1 l).

[0079] Example 7: Scratches were made on the surface of the AMF-Col prepared in Example 2, and the scratches were observed under a light microscope at 37°C. It was found that the scratched area was closed after 48 hours, proving that AMF-Col has self-healing ability ( Figure 1 l).

[0080] Examples 8-11: Assembly of AMF-Col under restricted thermodynamic conditions

[0081] Example 8: The AMF-Col prepared in Example 2 was placed in a constant temperature and humidity chamber with the temperature set to 37°C. A steam atmosphere was formed by placing an NH4HCO3 solution in the chamber. At a relative humidity of 40%, a CF-Col_40%RH assembly under restricted thermodynamic conditions was prepared.

[0082] Example 9: Using the same method as in Example 8, a CF-Col_60%RH assembly under restricted thermodynamic conditions was prepared at a relative humidity of 60%.

[0083] Example 10: Using the same method as in Example 8, a CF-Col_80%RH assembly under restricted thermodynamic conditions was prepared at a relative humidity of 80%.

[0084] Example 11: Using the same method as Example 8, a CF-Col_100%RH assembly under restricted thermodynamic conditions was prepared at a relative humidity of 100%.

[0085] Examples 12-14: Assembly of AMF-Col at different temperatures

[0086] Example 12: The AMF-Col prepared in Example 2 was placed in a constant temperature and humidity chamber with the humidity set to 60% RH. A steam atmosphere was formed by placing an NH4HCO3 solution in the chamber. At a temperature of 4°C, a CF-Col_4°C assembly was prepared.

[0087] Example 13: Using the same method as Example 12, at a temperature of 25°C, prepare the CF-Col_25°C assembly.

[0088] Example 14: Using the same method as Example 12, at a temperature of 37°C, prepare the CF-Col_37°C assembly.

[0089] Examples 15-18: Assembly of AMF-Col at different times

[0090] Example 15: The AMF-Col prepared in Example 2 was placed in a constant temperature and humidity chamber, the temperature was set to 37°C, the humidity was set to 60% RH, a steam atmosphere was formed by placing NH4HCO3 solution in the chamber, and the CF-Col_3h assembly was obtained after assembling for 3 hours.

[0091] Example 16: The same method as in Example 15 was used to obtain the CF-Col_6h assembly after 6 hours of assembly.

[0092] Example 17: The same method as in Example 15 was used to obtain the CF-Col_12h assembly after 12 hours of assembly.

[0093] Example 18: The same method as in Example 15 was used to obtain the CF-Col_24h assembly after 24 hours of assembly.

[0094] Example 19: Detecting the water content in the collagen network

[0095] The AMF-Col prepared in Example 2 was cut into 10 mm circular films, and the initial mass (W0) was weighed. Subsequently, the films were incubated in a constant temperature and humidity chamber under different humidity conditions for 24 hours, and the mass (Wt) of the films was weighed and recorded at designated time points (6, 12, and 24 h). After the incubation time (24 h), the samples were freeze-dried and the mass (We) was recorded. The results showed that CF-Col_40% rapidly dehydrated in less than 12 h, and the sample was eventually dry. CF-Col_60%RH experienced slight dehydration within the first 6 h, after which the water content in the network remained in equilibrium. CF-Col_80%RH showed slight swelling. However, CF-Col_100%RH underwent severe swelling and could no longer maintain its complete morphology. The water content in the collagen network was significantly increased ( Figure 2 b).

[0096] Example 20: Detection of collagen density in collagen network

[0097] The same method as in Example 19 was used to monitor the changes in collagen density in the collagen network. The results showed that due to the rapid dehydration inside the CF-Col_40%, the sample finally became dry and the collagen density increased sharply. There was a slight dehydration effect in the CF-Col_60%RH network, and its collagen density increased. CF-Col_80%RH showed slight swelling, and the collagen density dropped to 100 mg / cm 3 However, CF-Col_100%RH showed severe swelling, accompanied by a significant decrease in the collagen density in the network, which only reached 56.86 mg / cm after 6 h of culture. 3 ( Figure 2 c).

[0098] Examples 20-21: Characterization of micromorphology

[0099] Example 20: Take a small amount of CF-Col prepared in Example 8-18 and paste it on the conductive adhesive, and observe its surface morphology using a scanning electron microscope (SEM, S4800 Hitachi) ( Figure 2d). The results show that the surface structure of AMF-Col is relatively smooth, and the internal microfiber diameter is relatively uniform, about 10nm. The CF-Col obtained by restricted thermodynamic assembly has a relatively more obvious fibrous surface, among which the surface of CF-Col_40%RH is densely arranged with narrowly distributed fine fibers, with an average diameter of about 100nm and weak D-band characteristics. The surface of CF-Col_80%RH is loosely arranged with fine fibers with an average diameter of about 135nm, with weak D-band characteristics. The surface of CF-Col_60%RH cultured under 60%RH conditions is composed of densely arranged coarse fibers with a diameter distribution in the range of 400-500nm, and has obvious D-bands. The microscopic morphology of CF-Col assembled at different temperatures shows that the increase in temperature is conducive to the growth of collagen fibers. The fiber size of the assembly obtained at 37°C is coarser and more widely distributed. In addition, the increase in time is also conducive to the growth of collagen fibers, and its size increases with time.

[0100] Example 21: Take a small amount of CF-Col prepared in Examples 8-18 and place it on the sample stage, and observe its microstructure using small-angle X-ray (SAXS, BL19U2) ( Figure 2 h). The distance between the sample and the detector is 1950 mm. The sample is measured with an X-ray beam for several seconds until the scattered signal intensity reaches 10 5 The positions of all diffraction peaks observed in the SAXS sample can be explained by the periodic D band. The D band can be calculated according to the Bragg equation: D-banding = n2π / q; nm; where n is the order of the diffraction peak (1, 2, 3, etc.) and q is the position of the peak on the one-dimensional SAXS. The results show that CF-Col_60%RH, obtained by assembling at 37°C for 24 hours, exhibits a stronger scattering peak in the one-dimensional SAXS curve.

[0101] Example 22: Detection of fiber diameter and fiber size distribution

[0102] The SEM images of AMF-Col prepared in Example 2 and CF-Col prepared in Examples 8-18 were analyzed by ImageJ software, and the internal fiber diameters were measured and counted. The fiber diameter frequencies within each statistical range were fitted to obtain a fiber size distribution curve. The results showed that the average diameter of the CF-Col_60%RH fiber obtained by assembling at 37°C for 24 hours was larger, the diameter distribution was in the range of 400-500nm, the distribution was wider, and the fibers were closely arranged.

[0103] Example 23: Testing Suture Performance

[0104] The suturing performance of AMF-Col prepared in Example 2 and CF-Col prepared in Examples 8-18 were tested using a dynamic biomechanical tester (Electro-320) at a speed of 5 mm / min. The suturing strength test was conducted using 10-0 ophthalmic surgical sutures, one end of which was fixed on the wet sample at 10 mm from the edge, and the other end was fixed on the fixture of the tester. The results showed that CF-Col_60%RH, which was assembled at 37°C for 24 hours, showed better suturing performance, with a suturing resistance of 4.69 N / mm.

[0105] Example 24: Testing tensile properties

[0106] AMF-Col prepared in Example 2 and CF-Col prepared in Examples 8-18 were subjected to tensile tests at a speed of 5 mm / min using a dynamic biomechanical tester (Electro-320) until the sample broke, and the stress-strain curve was recorded. The results showed that the tensile strength first increased and then decreased with the increase of relative humidity. When the relative humidity was 60%, CF-Col_60%RH showed the best tensile properties, with a tensile strength of 5.97 MPa. The assembly incubated at 37°C for 24 hours showed excellent tensile properties because it had collagen fibers with thicker diameters and wider distribution.

[0107] Example 25: Preparation of heterogeneous fibrous structure collagen material

[0108] The customized mask was covered on the AMF-Col prepared in Example 2, and then exposed to a 365nm ultraviolet light source for cross-linking to fix the customized area. The same method as Example 9 was then used for subsequent restricted thermodynamic assembly. The customized area through photo-crosslinking maintained the stability of the fiber microstructure during the assembly process, and the area without photo-crosslinking formed large-scale fibrils during the assembly process. The collagen fiber structure was regulated by partitioning to obtain the heterogeneous structure collagen material HFs-Col ( Figure 5 a).

[0109] Example 26: Characterization of Surface Morphology of Heterogeneous Materials

[0110] The differences in fiber structure and surface morphology of different regions of the heterogeneous collagen material prepared in Example 25 were demonstrated by the reflected light during laser confocal imaging at 488nm excitation. The results showed that there was a significant difference in the fluorescence reflection intensity of AMF-Col and CF-Col, indicating that there may be differences in the internal assembly structure of the two regions. Further, according to their three-dimensional morphology and pseudo-color images, it can be clearly seen that the surface morphology of AMF-Col is relatively smooth, while the surface of CF-Col is rough and uneven, with large differences in terrain height. SEM and AFM characterization proved that the morphological differences between the two regions were caused by the different structures of the internal collagen fibers.

[0111] Examples 27-28: Evaluation of Mechanical Properties of Heterogeneous Materials

[0112] Example 27: A fence-type mask with a width of 3 mm was customized, and a heterogeneous collagen film with periodic stripes was prepared using Example 25. The collagen film was subjected to tensile property test using the same method as Example 24. The strip film was stretched in the longitudinal and transverse directions respectively, and the final stress-strain curve was recorded. The results showed that the homogeneous AMF-Col and CF-Col showed consistent tensile strength and Young's modulus in both perpendicular directions. However, the heterogeneous material HFs-Col with a stripe pattern showed anisotropic mechanical properties, and the mechanical properties depended on the stretching direction. When the stretching direction was parallel to the stripes, the ultimate stress, fracture strain, Young's modulus and toughness of HFs-Col were improved, and tended to approach CF-Col. On the contrary, when the stretching direction was perpendicular to the stripes, the strength and Young's modulus of HFs-Col were close to AMF-Col, but it was easier to break, that is, the elongation at break was lower.

[0113] Example 28: A fence-type mask with a width of 3 mm was customized, and a heterogeneous collagen membrane with periodic stripes was prepared using Example 25. The collagen membrane was tested for suturing performance using the same method as Example 23. When the 10-0 suture was pulled perpendicular to the stripe direction, the curve showed obvious fluctuations when passing through different areas, and the fluctuation range corresponded to the two areas of HFs-Col. When passing through the AMF-Col area of ​​HFs-Col, the suturing resistance was small, while when passing through the CF-Col area on HFs-Col, the suturing resistance became larger.

[0114] Examples 29-30: Cytocompatibility Assessment

[0115] Example 29: Evaluation of cell compatibility using human corneal epithelial cells HCECs. First, the adhesion of HCECs on AMF-Col and CF-Col was evaluated. 4HCECs were inoculated at a number of 1:1 / well and cultured in a 37°C cell culture incubator (5% CO2) for 24 hours, and then the cells were fixed. After being treated with 2.5% glutaraldehyde solution for 20 minutes, they were washed several times with PBS, and then gradually dehydrated with 50%, 70%, 90% and 100% ethanol for 10 minutes each time. Finally, they were dried in an oven at 60°C, and the adhesion state of the cells on the membrane after 24 hours was observed using a scanning electron microscope (S-4800, Hitachi). The scanned images showed that the cells were able to adhere well to the surface on both materials and appeared to be in a spreading state. Further quantification of the cell aspect ratio revealed that the cells grown on CF-Col with a clear fiber structure on the surface showed a larger aspect ratio, indicating that the fiber structure may affect the cell morphology.

[0116] Example 30: On the surfaces of AMF-Col and CF-Col, 2×10 4 HCECs were inoculated per well and then placed in a 37°C cell culture incubator (5% CO2) for culture until the specified time point. After 1, 3, and 5 days of culture, the proliferation rate of cells was evaluated using CCK8. At the predetermined time point, the culture medium containing fetal bovine serum was removed, and fresh culture medium containing 10% CCK8 reagent was added and cultured for 2 hours. 100 μL of the liquid was aspirated into a 96-well plate, and the absorbance at 450 nm was measured using a microplate reader. The OD value of the material group was recorded as OD1, and the OD values ​​of the TCP group and DMEM were OD2 and OD0, respectively. The cell viability was calculated by the formula. Cell viability = (OD1-OD0) / (OD2-OD0)×100%. After HCECs were incubated with Calcein AM / PI double staining buffer at 37°C for 15 minutes, fluorescence images were captured using a laser confocal microscope (Leica, DMi8). The fluorescence images showed that the cells continued to proliferate on the material during the culture period, and no obvious dead cells were found. It was demonstrated that this collagen material has good biocompatibility and can support cell adhesion and proliferation.

[0117] Example 31: Assessment of cell migration behavior

[0118] HCECs were plated at 5 × 10 4 / well were inoculated on the surface of AMF-Col and CF-Col and placed in a 37℃ cell culture incubator (5% CO2) for culture. After the cells covered the surface of the material, a 200μL pipette tip was used to scratch the cell layer on the surface of the sample, and then the suspended cells were rinsed off with PBS. The cell migration state was observed and recorded using an inverted fluorescence microscope within 0, 24, 48 and 72h after the scratch was completed. ImageJ was used to quantify the migration efficiency of cells at different times. Cell migration rate = A1 / A0×100%, where A0 is the initial scratch area and A1 is the immediate cell migration area. Microscopic images show that cells inoculated on the two materials and on the well plate showed different migration rates. Both AMF-Col and CF-Col can support the rapid migration of HCECs. The scratch area was filled on the third day, and some areas in the well plate were still not filled by cell migration. The results showed that the cell migration rate on AMF-Col and CF-Col was significantly higher than that on the well plate, indicating that this collagen material can promote cell migration and that the implant is beneficial to the repair of the corneal epithelium in vivo.

[0119] Example 32: In vivo repair of rabbit corneal lamellar defects

[0120] Adult male New Zealand rabbits were used for in vivo experiments. A 7-mm trephine (Suzhou Union Medical Device Co., Ltd.) was used to create a defect of approximately 200 μm in thickness in the rabbit eye, and lamellar keratectomy was performed at this depth with a scalpel. The constructed heterogeneous artificial cornea HFs-ACSs was used as the experimental group to fill and suture the defect site, and the commercial decellularized porcine corneal CM was used as the positive control group to fill and suture the defect site. The group without implanted materials was used as a blank control. The surgery was performed under a sterile environment, and general anesthesia was performed by intramuscular injection of a mixed solution of Shutai: Suminxin = 1:3. In addition, the eyes were locally anesthetized with oxybuprocaine hydrochloride eye drops. Conventional optical observation with a slit lamp showed that the blank group had slight stromal edema within 1 week after tissue injury, and obvious defect boundaries could still be observed 8 weeks after surgery. Both HFs-ACSs and CM produced a certain immune response after implantation. Fluorescence images taken by a slit lamp with a cobalt blue filter showed that the epithelialization rate of the HFs-ACSs and CM implant groups was comparable, and both completed epithelialization in about 4 weeks. The front-end optical coherence tomography (AS-OCT) was further used to observe the cross-section of the corneal tissue, evaluate the fusion of the implant material with the surrounding tissue, and study the recovery of corneal thickness based on corneal topography. The results showed that the blank control group showed a phenomenon of stromal thinning after surgery, and stromal defects were clearly observed. The damaged corneal stroma still could not recover to normal thickness at 8 weeks, which was about 305±10μm. For the HFs-ACSs and CM groups, at 4 weeks, OCT observed that the boundary between the implant material and the host tissue became blurred, indicating the fusion of the implant material and the tissue. After 8 weeks, the cornea was observed to be completely epithelialized on the upper surface of the HFs-ACSs and CM implant sites, and the corneal stromal thickness also recovered to the normal level of healthy cornea, which was 420±24μm and 495±9μm, respectively, of which the thickness of the healthy cornea was about 423±18μm.

[0121] Example 33: Rabbits were euthanized and samples were collected 8 weeks after surgery. Eyeball tissues were fixed with 4% (v / v) paraformaldehyde for 48 h, then dehydrated, embedded and sliced. H&E staining was performed and observed using a hematoxylin and eosin kit. Immunofluorescence staining such as α-SMA / DAPI and ZO-1 / DAPI was performed according to the operating procedures and observed under a fluorescence microscope. The results of H&E staining showed that the matrix defects in the blank control group were replaced by proliferating epithelial tissue, and the overall appearance was uneven epithelialized tissue. In the experimental group implanted with HFs-ACSs, the implanted materials showed good tissue compatibility, and no obvious inflammatory cell aggregation or neovascularization was observed. Moreover, a relatively complete new corneal epithelium was formed on the implanted HFs-ACSs, and its thickness was comparable to that of the normal corneal epithelium. In addition, HFs-ACSs were well integrated with the underlying host matrix tissue. The results of fluorescent staining images showed that HFs-ACSs did not cause significant activation of myofibroblasts after implantation, and could support the formation of tight junctions in the regenerated epithelial layer.

[0122] Example 34: Assessment of postoperative visual function reconstruction

[0123] Rabbits were fed with regular food for 23 days after surgery. They were fed with dried timothy grass for three days before the foraging behavior test to build cognition. Then they were starved for 24 hours. Behavioral observations were carried out on the second day of the starvation treatment. In order to avoid possible interference of rabbits' sense of smell during the experiment, fake timothy grass and fake flower bouquets were used as reference objects. All animals started from the same starting point, and the time from the starting point to finding the target was recorded. In order to avoid accidental phenomena in the experiment, the positions of fake timothy grass and fake flower bouquets were exchanged and repeated to observe their foraging behavior, and the recovery of visual function by the material was evaluated. The foraging behavior results showed that both the healthy cornea group and the two groups with implanted materials could quickly find the target, while the blank control group without implanted materials was in a relatively disordered search state, requiring more time and a longer path to locate the target, which was significantly different from the other three groups. The reason for this phenomenon may be that the control group cannot restore the corneal stroma thickness to the normal corneal stroma thickness, and refractive errors will occur after surgery, thus affecting its visual function.

[0124] In the description of the present invention, the terms "comprises", "includes" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the statement "comprising a reference structure" do not exclude the presence of other identical elements in the process, method, article or device comprising the elements. It should be noted that, in this article, relational terms such as "first", "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations.

[0125] The above-described embodiments are only specific implementation methods of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be thought of by any technician familiar with the art within the technical scope disclosed in the present application without creative work should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims in the present application.

Claims

1. A method for preparing a heterogeneous fiber microstructure collagen artificial cornea, characterized in that: The preparation method comprises: (1) dissolving type I collagen and forming an electric field-triggered kinetically assembled collagen film through electrodeposition reaction; (2) Covering the collagen film with electric field-triggered dynamic assembly with a preset photomask and then exposing it to a UV light source for local photocrosslinking; (3) Placing the collagen film that has undergone local photocrosslinking under constant temperature and humidity conditions to induce continuous thermodynamic assembly of uncrosslinked collagen: placing it under constant temperature and humidity conditions for 3-30 hours at a temperature of 4-45°C and a relative humidity of 40%-100% in the constant temperature and humidity space.

2. The method for preparing the heterogeneous fiber microstructure collagen artificial cornea according to claim 1, characterized in that: The kinetically assembled collagen membrane was locally UV-crosslinked, and the photocrosslinking conditions used were a wavelength of 365 nm, an irradiation time of 12 h, and a distance of 20–30 cm from the sample; The collagen membrane after local photocrosslinking is placed under constant temperature and humidity conditions for further assembly at a temperature of 25-40°C for 6-24 hours. An ammonium salt solution is placed in the constant temperature and humidity space; the relative humidity is controlled at 40%-80%, and the dense stacking state of the fibers is maintained while controlling the diameter of the assembled fibers.

3. The method for preparing the heterogeneous fiber microstructure collagen artificial cornea according to claim 1, characterized in that: The collagen membrane after local photocrosslinking is placed under constant temperature and humidity conditions at 35-37° C. for 12-24 hours, and the relative humidity is controlled at 40%-60%. The ammonium salt solution placed in the constant temperature and humidity space is NH4HCO3 solution.

4. The method for preparing the heterogeneous fiber microstructure collagen artificial cornea according to claim 3, characterized in that: The concentration of NH4HCO3 solution is 50-200mM.

5. The method for preparing the heterogeneous fiber microstructure collagen artificial cornea according to claim 1, characterized in that: The preparation method of the collagen film comprises: Dissolve type I collagen, add glacial acetic acid to make its pH acidic; add hydrogen peroxide to obtain collagen electrolyte; The three-electrode system of electrodeposition is used to establish a pH gradient by utilizing electrode reaction, so that the collagen undergoes a phase transition, from a collagen solution to a collagen gel membrane AMF-Col. The reaction equations at the anode and cathode are as follows: Anode: 2H2O–4e - →4H + +O2; Cathode: 2H2O+4e - →4OH-+2H2.

6. The method for preparing the heterogeneous fiber microstructure collagen artificial cornea according to claim 1, characterized in that: The collagen membrane assembled by electric field-triggered dynamics is locally exposed to a UV light source for cross-linking, thereby fixing the collagen fiber structure in the customized area; The original fiber microstructure of the customized area that was photocrosslinked remained unchanged during the continued assembly process, and the area that was not photocrosslinked formed large-scale collagen fibers during the assembly process according to the following method.

7. The method for preparing a heterogeneous fiber microstructure collagen artificial cornea according to any one of claims 1 to 6, characterized in that: The riboflavin photo-crosslinking method was used, and the wavelength of ultraviolet light used for photo-crosslinking was 365nm.

8. A heterogeneous fiber microstructure collagen artificial cornea, characterized in that: Using the preparation method described in any one of claims 1 to 7, a collagen fiber network with spatial heterogeneity is obtained.

9. The heterogeneous fiber microstructure collagen artificial cornea according to claim 8, characterized in that: The diameter of collagen fibers in the photocrosslinked area is maintained at 10-20 nm, and the diameter of collagen fibers in the non-photocrosslinked area is 400-500 nm. The packing density of the collagen network is not less than 230 mg / cm 3 .

10. The use of the heterogeneous fiber microstructure collagen artificial cornea according to claim 8, characterized in that: The application of the heterogeneous fiber microstructure collagen artificial cornea in repairing corneal lamellar defects.

11. The use according to claim 10, characterized in that: The heterogeneous fiber microstructure collagen artificial cornea described in claim 8 or 9 is directly used as an implant material for repairing corneal defects to promote the migration of corneal epithelial cells to the defect site, thereby achieving epithelialization of the corneal defect site; or to help the regeneration of the corneal stroma layer to restore the cornea to a healthy level.

Citation Information

Cited By

  • Ultra-low swelling artificial cornea imitating natural corneal fiber arrangement and preparation method

    CN120305460B

  • Preparation method of bionic cornea stroma lens capable of being used for refractive correction

    CN120754321A

  • A method for manufacturing a biomimetic corneal stromal lens useful for refractive correction

    CN120754321B